PRINSIP KEMANDIRIAN NOTARIS DALAM PEMBUATAN AKTA OTENTIK - FRANSISKUS SINAGA (PREMISE LAW JURNAL, 2015)
A notary is expected to be honest, accurate, independent, impartial, and able to keep the clients interest in legal act of Article 16 (a) of UUJN. What it means by independence is that a notary in doing his notarial duty should be neutral and impartial. The independence of a Notary is reflected in the skill and supported by science, experience, sophisticated skill, and good moral integrity. A notary must know the scope of his authority, obey the prevailing regulations, and know what he can do and what he cannot do. The sanctions imposed on a notary are administration sanction, civil sanction, and criminal sanction, as it is stipulated in Article 84e and Article 85 of UUJN, while criminal sanction, stipulated in Article 63, paragraph 2 of the Penal Code, states that when there is a criminal act which can be criminalized according to specific crime, besides general crime, the specific crime is used. Kata Kunci : Independence of a Notary